Sensitive and selective detection of DNA fragments associated with Ganoderma boninense by DNA-nanoparticle conjugate hybridisation - Ekta Rani; Mohshim, Siti Akhtar; Yusof, Nor Hidayat; Ahmad, Muhammad Zamharir; Goodacre, Royston; Alang Ahmad, Shahrul Ainliah; Wong, Lu Shin (Springer New York LLC, 2020)
A colourimetric assay for the detection of DNA fragments associated with the oil palm pathogen Ganoderma boninense and other fungi DNA is reported. The assay is based on the aggregation of DNA-nanoparticle conjugates in the presence of complementary DNA from the target organism. Here, various designs of DNA-nanoparticle conjugates were evaluated, and it was found that the best design gave a visually observable colour change with as little as 2 pmol of double-stranded DNA analyte even in the presence of a large excess of a mixture of non-complementary DNA. Overall, this label-free system is rapid, sensitive, selective, simple in design, and easy to carry out. It does not require specialist equipment or specialist training for the interpretation of the results, and therefore has the potential to be deployed for agricultural diagnostics in the field.